2019
DOI: 10.1097/dad.0000000000001266
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf-1 Expression in Androgenetic Alopecia and Alopecia Areata in Male Patients

Abstract: Background: Androgenetic alopecia (AGA) results from shortening of the anagen phase of the hair cycle and, subsequently, miniaturization of hair follicles. Alopecia areata (AA) is a disease of autoimmunity where T cells attack anagen hair follicles and shows multifactorial etiology. Dickkopf-1 (DKK-1) is a gene that is responsible for transformation of anagen to catagen, which suggests that it is involved in development of both diseases. Objectives: To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Moreover, the anti-DKK1 neutralizing antibody substantially decreased the inhibition of ORS cells’ growth. As previously mentioned, DKK1 concentration is increased in the bald scalp of AGA patients compared with the haired scalp of AGA patients [ 10 , 40 ]. Besides, DHT-influenced DKK1 augmentation has been demonstrated to enhance the apoptosis of keratinocytes in vitro [ 10 ].…”
Section: Dkk1 Implication In Agamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the anti-DKK1 neutralizing antibody substantially decreased the inhibition of ORS cells’ growth. As previously mentioned, DKK1 concentration is increased in the bald scalp of AGA patients compared with the haired scalp of AGA patients [ 10 , 40 ]. Besides, DHT-influenced DKK1 augmentation has been demonstrated to enhance the apoptosis of keratinocytes in vitro [ 10 ].…”
Section: Dkk1 Implication In Agamentioning
confidence: 99%
“…As previously mentioned, DKK1 overexpression is evidenced in the scalp of patients with AGA. Thus, it represents the key protein in the development of AGA [ 40 ].…”
Section: The Importance Of Wnt/β-catenin Signaling In Hair Growthmentioning
confidence: 99%
“…Subsequent studies have reported that genetic ablation of β-catenin gene in epidermis leads to the failure of placode morphogenesis in mice [ 24 ], suggesting the importance of Wnt signals in hair development. Andl and colleagues [ 35 ] generated transgenic mice having epidermal basal cell-specific ectopic expression of Dickkopf 1 (DKK1), which inhibits Wnt action [ 36 , 37 , 38 , 39 , 40 ] by binding with LRP co-receptor, to evaluate the role of Wnt in HF. This study reported that skin-specific overexpression of DKK1 leads to an early and complete block in the development of skin appendages including all types of hair follicles, thus suggesting the essential roles of WNT proteins in follicle development.…”
Section: Role Of Wnt/β-catenin Signaling In Hair Growthmentioning
confidence: 99%
“…This study reported that skin-specific overexpression of DKK1 leads to an early and complete block in the development of skin appendages including all types of hair follicles, thus suggesting the essential roles of WNT proteins in follicle development. A significant increase in DKK1 immunostaining was found in leisonal scalp biopsies taken form patients with androgenic alopecia and alopecia areata as compared to healthy control volunteers [ 35 ]. The administration of recombinant human DKK-1 (rhDKK-1) into mouse hypodermis resulted in final hair follicle length and premature onset of catagen, a key feature of male pattern baldness.…”
Section: Role Of Wnt/β-catenin Signaling In Hair Growthmentioning
confidence: 99%
“…19,20 DKK-1 is of special interest since a significant increase in DKK1 immunostaining was found in lesional scalp biopsies taken from patients with androgenic alopecia and alopecia areata when compared to healthy control volunteers. 21 It was reported that the administration of recombinant human DKK-1 (rhDKK-1) into mouse hypodermis resulted in premature onset of catagen, a key feature of male pattern baldness. Injection of neutralizing DKK-1 antibody, on the contrary, delayed the anagen to catagen transition in mice.…”
Section: Introductionmentioning
confidence: 99%